2019
DOI: 10.1039/c9nj02287b
|View full text |Cite
|
Sign up to set email alerts
|

Direct ethanol condensation to diethyl acetal in the vapour phase at atmospheric pressure over CuNP/SBA-15 catalysts

Abstract: Of the biomass valorization technologies, bioethanol production and its selective conversion to diethyl acetal is of utmost importance to meet the increasing demand for bio-fuel additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The DEE formation rates achieved in this study and those reported in previous works are listed in Table S1. The DEE formation rate achieved by our system (670 mmol g cat −1 h −1 ) is higher than those of the flow systems using heterogeneous catalysts (5–12 mmol g cat −1 h −1 ), [6b–d] photocatalytic systems (8–158 mmol g cat −1 h −1 ), [7a–d] and liquid phase reactions with homogeneous catalysts (13 mmol g cat −1 h −1 ) [18] . The high formation rate suggested that the electrocatalytic approach is potentially practical to synthesize DEE.…”
Section: Resultsmentioning
confidence: 73%
“…The DEE formation rates achieved in this study and those reported in previous works are listed in Table S1. The DEE formation rate achieved by our system (670 mmol g cat −1 h −1 ) is higher than those of the flow systems using heterogeneous catalysts (5–12 mmol g cat −1 h −1 ), [6b–d] photocatalytic systems (8–158 mmol g cat −1 h −1 ), [7a–d] and liquid phase reactions with homogeneous catalysts (13 mmol g cat −1 h −1 ) [18] . The high formation rate suggested that the electrocatalytic approach is potentially practical to synthesize DEE.…”
Section: Resultsmentioning
confidence: 73%
“…However, the conversion of ethanol was basically unchanged, but the selectivity of DEC began to decrease when the reaction temperature was further increased. This may contribute to increasing reaction temperature to some extent: ethanol is more oxidized to acetaldehyde leading to producing DEE by aldol condensation reaction . Therefore, the optimal reaction temperature is selected to be 383 K.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This may contribute to increasing reaction temperature to some extent: ethanol is more oxidized to acetaldehyde leading to producing DEE by aldol condensation reaction. 42 Therefore, the optimal reaction temperature is selected to be 383 K.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the conversion of ethanol over TiO 2 and Au/TiO 2 affords acetaldehyde or further oxidation products but no coupling products, mainly because these catalysts lack the surface active sites required for coupling. As the direct conversion of ethanol to 1,1-diethoxyethane (1,1-DEE) involves oxidation and acetalization, catalysts promoting this one-pot transformation should feature both acidic sites and oxidizing functions . Fan et al showed that the intercalation of Ag atoms into the tunnels of the hollandite manganese oxide (HMO) structure resulted in the formation of sites with enhanced Lewis acidity to achieve an ethanol-to-1,1-DEE conversion selectivity of ≥85% .…”
Section: Introductionmentioning
confidence: 99%